A case of asbestos-related lung cancer: critical analysis and discussion of the medico-legal aspects - Dario MAZZARELLA; Pasquale BUONGIORNO; Pasquale VIETRI (GIornale Italiano di Psicologia e Medicina del Lavoro)
Asbestos is a naturally occurring fibrous silicate mineral. There are six types, all of which are com- posed by long and thin fibrous crystals that can be released into the atmosphere by abrasion and other processes. Asbestos-related diseases include malignant conditions such as pleural and peri- toneal mesothelioma and lung cancer, and possibly ovarian and laryngeal cancers. Nonmalignant asbestos diseases include asbestosis, chronic obstructive pulmonary disease, pleural plaques, pleural thickening, pleural effusion and atelectasis. We present a case of asbestos-related lung cancer (adenocarcinoma originating in the right lower lobe) in a carpenter employed for fifteen years (from 1966 to 1981) in a train carriage manufacture. We analyzed the occupational history of the worker, and carried out a critical analysis of diagnostic criteria needed to recognize the causal relationship between exposure and disease, in the context of the medical examination for worker’s compensation claim. The medico-legal evaluation made by the Medical Director employed at the Italian National Institute for Insurance against Accidents at work and occupational diseases (INAIL) resulted in the recognition of the disease as asbestos-rela- ted occupational cancer. In this case report, the occupational history, the presence of pleural plaques that are a pathognomonic indicator of exposure to asbestos, were sufficient for its recognition as an occupational disease related to asbestos, despite the concausal role played by cigarette smoking.